2004
DOI: 10.3748/wjg.v10/i4/550
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of N-myc downstream-regulated gene 1 overexpression with progressive growth of colorectal neoplasm

Abstract: NDRG1 gene may play an important role in colorectal carcinogenesis. In addition, NDRG1 may be a putative tumor metastasis promoter gene and is regarded as one of the molecular biological markers that can forecast early metastasis of CRCs. NDRG1 gene in the metastatic sites of regional lymph nodes may preserve its expression characteristics in the primary sites of CRCs to some extent. The expression of NDRG1 is not affected by sex, age and histological types. The role of NDRG1 in tumor metastatic process can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Earlier publications had reported down regulation of NDRG1 expression in colon, breast, and prostate cancers [2,[14][15][16] . In contrast, recent studies reported increased expression of NDRG1 protein in malignancy including skin, brain, lung, colon, breast and prostate cancers [17][18][19] . The expression of NDRG1 in colon cancer has also been controversial.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Earlier publications had reported down regulation of NDRG1 expression in colon, breast, and prostate cancers [2,[14][15][16] . In contrast, recent studies reported increased expression of NDRG1 protein in malignancy including skin, brain, lung, colon, breast and prostate cancers [17][18][19] . The expression of NDRG1 in colon cancer has also been controversial.…”
Section: Introductionmentioning
confidence: 76%
“…Despite NDRG1 upregulation in many other tumor types [10,17,18,23] , NDRG1 expression in colorectal cancer has been controversial [2,19,20] . Wang et al [19] demonstrated that NDRG1 expression was increased in colorectal carcinogenesis and correlated with lymph node metastasis in a Chinese population and suggested that NDRG1 might be a possible marker for prediction of early metastasis of colorectal cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although increased NDRG1 protein expression has been reported for different types of tumor cells such as human HCC and colorectal tumors (11,49), other studies showed a decrease in its expression level such as in metastasizing colon cancer cell lines (50). Low-grade astrocytoma (LGA) displayed a lower level of NDRG1 mRNA and protein expression than GBM samples from patients (8).…”
Section: Discussionmentioning
confidence: 99%
“…NDRG1/Cap43 is expressed at lower levels in tumor cells including prostate, breast and colorectal cancers than in normal tissue (2,4,12), and can suppress metastasis by inducing cell differentiation and reversing the metastatic phenotype (13,14). However, NDRG1/Cap43 is highly expressed in certain tumors, such as hepatocellular and colorectal carcinoma (15,16). The NDRG1/Cap43 expression is positively associated with tumor angiogenesis in cervical adenocarcinoma (17).…”
Section: Introductionmentioning
confidence: 99%